Business Hotel Di Pekanbaru Dengan Pendekatan Arsitektur Tropis - Lesmana, Andri; Aldy, Pedia; S, Mira Dharma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Pekanbaru is the capital of Riau province which became one of the provinces whose economic growth is very rapid. From small economy sectors even up to business and foreign investors are in Pekanbaru. Pekanbaru also has become a destination town investors both from within the country and also abroad have been widely developed in the city of Pekanbaru. But the facilities and space requirements to support the economy really was little. Therefore, the hotel business is becoming one of the alternatives for developing the economic sector in the city of Pekanbaru. In the design of the hotel business, applied design approach emphasizes the principles of tropical architecture with the aim of building that is designed into a building that can decrease bad influence on the environment, nature, and human and produce a better and more healthy. However, to support this scheme deeper then also applied the concept of